Sympathie mit dem Tode On Nietzsche, Mishima and the “free death” - Giacomelli, Alberto (Scenari, 2021)
This essay aims to focus on some affinities and differences between the Japanese writer Yukio Mishima’s literary, theatrical and cinematographic work and Nietzsche’s thoughts on the theme of “free death”. The aim of this intercultural reflection is to set up an aesthetic and ethical-existential comparison between two of the major interpreters of modernity, respectively European and Japanese. While Nietzsche’s reflection on suicide is influenced solely by Western philosophical tradition, Mishima’s artistic and bodily meditation on seppuku (切腹) is characterized by the tension between European sensibility and Japanese cultural identity, which coexist and contrast in the same time. Mishima hybridises, in his artistic-literary work, the traditional “Way of the Warrior” (Bushidō 武士道), precepts of Hagakure (葉隠), Zen Buddhism and Japanese nationalist radicalism with the values of heroic Greece, Wagner’s romanticism and a peculiar reading of Nietzsche’s philosophy. How does Mishima interpret Zarathustra’s warning to die “at the right time”? How does Nietzsche’s thought, through Mishima’s reading, come into contact and intertwine with Japanese art and traditional thought? What is the relationship between Nietzsche’s aesthetics, existentialism and Zen Buddhism? By analysing some important relations such as that between love, old age and death and that between freedom, obedience and subjectivity I will try to go through these questions.